Powtoon sebagai Media Alternatif Bimbingan Belajar Online SDN Curahsawo 3 Kabupaten Probolinggo - Afib Rulyansah; Ribut Prastiwi Sriwijayanti; Ani Anjarwati; Pance Mariati (Indonesia Berdaya, 2022)
The spread of COVID-19 has made it difficult to teach in the classroom. One way to avoid this challenge is through online virtual classes. consequently, the media must play a role in ensuring that students are engaged in their studies. This community service aims to empower Powtoon in virtual learning at SDN Curahsawo 3, Probolinggo Regency. The PKM project is designed to help teachers use technology more effectively when creating instructional videos that can be used during the learning process. This community service project is divided into four parts: observation, looking at the problem, looking for solutions, and finding. This service involves 28 first graders. Adopting Powtoon media has many benefits, such as increasing student enthusiasm, making learning more interesting, and helping students learn faster. In addition, the teacher's enthusiasm for developing Powtoon content is evident.  Abstrak: Penyebaran COVID-19 telah membuat sulit untuk mengajar di kelas. Salah satu cara untuk menghindari tantangan ini adalah melalui kelas virtual online. Akibatnya, media harus memainkan peran dalam memastikan bahwa siswa terlibat dalam studi mereka. Pengabdian masyarakat ini bertujuan untuk memberdayakan powtoon dalam pembelajaran virtual di SDN Curahsawo 3 Kabupaten Probolinggo. Proyek PKM dirancang untuk membantu guru menggunakan teknologi secara lebih efektif ketika membuat video pembelajaran yang dapat digunakan selama proses pembelajaran. Proyek pengabdian masyarakat ini dibagi menjadi empat bagian: observasi, melihat masalah, mencari solusi, dan mengevaluasi. Layanan ini melibatkan 28 siswa kelas satu. Mengadopsi media Powtoon memiliki banyak manfaat, seperti meningkatkan semangat siswa, membuat pembelajaran lebih menarik, dan membantu siswa belajar lebih cepat. Selain itu, antusiasme guru untuk mengembangkan konten Powtoon terlihat jelas.